2008
DOI: 10.1016/j.neuropsychologia.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and involuntary attention affect face discrimination differently

Abstract: Do voluntary (endogenous) and involuntary (exogenous) attention have the same perceptual consequences? Here we used fMRI to examine activity in the fusiform face area (FFA-a region in ventral visual cortex responsive to faces) and frontal-parietal areas (dorsal regions involved in spatial attention) under voluntary and involuntary spatial cueing conditions. The trial and stimulus parameters were identical for both cueing conditions. However, the cue predicted the location of an upcoming target face in the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
(54 reference statements)
5
28
0
Order By: Relevance
“…These results provide further evidence that voluntary and involuntary attention have different neural substrates (Kincade et al, 2005; Landau et al, 2007; Esterman et al, 2008). Allocation of voluntary attention can improve processing at an attended location at the cost of impaired processing in other locations (Bashinski and Bacharach, 1980; Posner et al, 1980).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These results provide further evidence that voluntary and involuntary attention have different neural substrates (Kincade et al, 2005; Landau et al, 2007; Esterman et al, 2008). Allocation of voluntary attention can improve processing at an attended location at the cost of impaired processing in other locations (Bashinski and Bacharach, 1980; Posner et al, 1980).…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, attention can be captured in an involuntary fashion by a salient event at a spatial location, even when that location is not task-relevant (Yantis and Jonides, 1990). These two forms of attention (voluntary and involuntary, or endogenous and exogenous) have different consequences for the processing of visual stimuli (Prinzmetal et al, 2005; Prinzmetal et al, 2008) and are associated with different neural mechanisms (Kincade et al, 2005; Landau et al, 2007; Esterman et al, 2008). Additionally, voluntary and involuntary attention differ in their time course.…”
Section: Introductionmentioning
confidence: 99%
“…Or are faces just more robust to manipulations of spatial attention than non-face stimuli [22][25]? We reconcile this issue in the present study by demonstrating for the first time reliable effects of both spatial and temporal attention on sex-classification processes within a behavioural task [16], [17], [26].…”
Section: Introductionsupporting
confidence: 68%
“…Where fMRI studies have documented clear and replicable effects of spatial attention on the neural response for faces [18], [20], [30], [31], [63], the behavioural evidence for this position has been inconsistent [13][17], [26]. In the present study, we have reconciled this issue by demonstrating a reliable effect of both spatial and temporal attention on an overt behavioural response to a face target.…”
Section: Discussionmentioning
confidence: 51%
“…However, previous studies using similar designs have reported behavioral differences between voluntary and involuntary attention (e.g., Prinzmetal, McCool, & Park, 2005;Prinzmetal, Park, & Garrett, 2005), as well as differences in neural activity, measured using fMRI (Esterman et al, 2008) and EEG (Landau, Esterman, Robertson, Bentin, & Prinzmetal, 2007).…”
Section: Methodsmentioning
confidence: 92%